Monkeys (Macaca mulatta) Rank Lists Using Multiple Cognitive Mechanisms Simultaneously. - Sammeroff, Rael; Hampton, Robert R. (Journal of Comparative Psychology, 2025)
Memorizing the relations between items and learning relational rules are two ways in which sets of items can be ranked. We investigated the interaction of these types of learning in a series of five experiments with six adult male rhesus monkeys. We presented monkeys with three types of image sets. Scene sets were random images of natural scenes or cityscapes with no perceptually evident pattern by which to rank them. Relations among these images had to be learned through trial and error. Patterned sets were shapes that varied systematically along a physical dimension such as size such that a single rule for ranking them could be applied across images. Disordered sets were the same as Patterned sets, but monkeys were trained to rank them in an arbitrary order that was not consistent with differences along a physical dimension. Monkeys learned Scene sets more quickly than Patterned sets and Disordered sets, suggesting that monkeys memorize the relations between images relatively easily. In follow-up experiments, we found that monkeys also learned rules for the Patterned sets, indicated by the fact that they generalized performance to novel images and reversed ranks across the whole set after training with a single reversed pair. In Experiments 4 and 5, we investigated the interaction of memorization and relational rule learning with compound image sets that included both systematic physical variation and arbitrary visual content. We found further evidence that monkeys ordered images by both memorization and rules.